2022
DOI: 10.1371/journal.pone.0272576
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effects of human activities and climate variability on runoff changes using variable infiltration capacity model

Abstract: Detecting and assessing changes in the hydrologic cycle and its response to a changing environment is essential for maintaining regional ecological security and restoring degraded ecosystems. There is no clear scientific evidence on the effects of human activities and climate variability on runoff and its components in typical arid areas. Therefore, in this study, a heuristic segmentation algorithm, a variable infiltration capacity model (VIC), and remote sensing data to quantify the effects of human activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Conversely, prolonged dry periods in summer can result in a drop in water levels (Kubicz, 2019;Ahmad et al, 2021;Belemtougri et al, 2021;Merz et al, 2021). The global climate patterns, particularly precipitation and air temperature, have a notable effect on river water levels (Dettinger, Diaz, 2000;Chang et al, 2016;Ghotbi et al, 2020;Wei et al, 2020;Lv et al, 2021;Bao, Ding and Han, 2022;Li et al, 2023). The data obtained from meteorological monitoring stations on precipitation and air temperature in the study area, as shown in Figure 3, align well with the measurements recorded by the piezometer.…”
Section: The Variations Of Groundwater and Surface Water Levelsupporting
confidence: 76%
“…Conversely, prolonged dry periods in summer can result in a drop in water levels (Kubicz, 2019;Ahmad et al, 2021;Belemtougri et al, 2021;Merz et al, 2021). The global climate patterns, particularly precipitation and air temperature, have a notable effect on river water levels (Dettinger, Diaz, 2000;Chang et al, 2016;Ghotbi et al, 2020;Wei et al, 2020;Lv et al, 2021;Bao, Ding and Han, 2022;Li et al, 2023). The data obtained from meteorological monitoring stations on precipitation and air temperature in the study area, as shown in Figure 3, align well with the measurements recorded by the piezometer.…”
Section: The Variations Of Groundwater and Surface Water Levelsupporting
confidence: 76%
“…Then, the heuristic segmentation algorithm was used to test and review the final variation points. The computational principle of the heuristic segmentation algorithm is briefly described below [31].…”
Section: Comprehensive Diagnosismentioning
confidence: 99%
“…Distinguishing the quantitative impacts of global climate change and regional human activities on regional climate change is essential for determining the dominant factor influencing regional climate change. At present, many studies have attempted to quantify the contributions of global climate change and human activities to hydrological fields (Bao et al., 2022; Q. Li, Wang, et al., 2021; Q. Li, Li, et al., 2021; Zhang et al., 2020) or hydroclimatic fields (Dai, 2021; Wu et al., 2020), such as runoff and evapotranspiration. Most of them used linear correlation, statistical methods of land surface assimilation data, few of them were able to reliably and scientifically answer this question in relation to arid endorheic regions (D. Peng et al., 2018) by using dynamic land‐atmosphere interaction climate models, and most climate models lacked a comprehensive description of regional human activities, especially the irrigation process, which is a key human activity in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Distinguishing the quantitative impacts of global climate change and regional human activities on regional climate change is essential for determining the dominant factor influencing regional climate change. At present, many studies have attempted to quantify the contributions of global climate change and human activities to hydrological fields (Bao et al, 2022;Q. Li, Wang, et al, 2021;Q.…”
mentioning
confidence: 99%